Characterization and pathogenicity evaluation of recombinant novel duck reovirus isolated from Southeast China - Yang, Huihu; Zhang, Wandi; Wang, Meihong; Yuan, Sheng; Zhang, Xuelian; Wen, Feng; Guo, Jinyue; Mei, Kun; Huang, Shujian; Li, Zhili (Frontiers in Veterinary Science, 2023)
The novel duck reovirus (NDRV) emerged in southeast China in 2005. The virus causes severe liver and spleen hemorrhage and necrosis in various duck species, bringing serious harm to waterfowl farming. In this study, three strains of NDRV designated as NDRV-ZSS-FJ20, NDRV-LRS-GD20, and NDRV-FJ19 were isolated from diseased Muscovy ducks in Guangdong and Fujian provinces. Pairwise sequence comparisons revealed that the three strains were closely related to NDRV, with nucleotide sequence identities for 10 genomic fragments ranging between 84.8 and 99.8%. In contrast, the nucleotide sequences of the three strains were only 38.9–80.9% similar to the chicken-origin reovirus and only 37.6–98.9% similar to the classical waterfowl-origin reovirus. Similarly, phylogenetic analysis revealed that the three strains clustered together with NDRV and were significantly different from classical waterfowl-origin reovirus and chicken-origin reovirus. In addition, the analyses showed that the L1 segment of the NDRV-FJ19 strain was a recombinant of 03G and J18 strains. Experimental reproduction of the disease showed that the NDRV-FJ19 strain was pathogenic to both ducks and chickens and could lead to symptoms of hemorrhage and necrosis in the liver and spleen. This was somewhat different from previous reports that NDRV is less pathogenic to chickens. In conclusion, we speculated that the NDRV-FJ19 causing duck liver and spleen necrosis is a new variant of a duck orthoreovirus that is significantly different in pathogenicity from any previously reported waterfowl-origin orthoreovirus.